Long-term sustained release Poly(lactic-co-glycolic acid) microspheres of asenapine maleate with improved bioavailability for chronic neuropsychiatric diseases - Junqiu Zhai; Yu-e Wang; Xiangping Zhou; Yan Ma; Shixia Guan (Taylor & Francis Group, 2020)
Schizophrenia and bipolar disorder are severe chronic neuropsychiatric diseases, affecting hundreds of millions of people worldwide. Asenapine maleate (ASM) has been demonstrated as a safe and effective therapeutic agent under twice-daily administration. However, lower compliance is observed when patients are treated with ASM, which significantly limits its application in schizophrenia and bipolar disorder. Moreover, the low bioavailability of ASM caused by first-pass metabolism and poor aqueous solubility also impairs the treatment effect. A formulation of ASM with the property of long-term sustained release and improved bioavailability can be a solution to overcome these weaknesses. In this article, we prepared ASM-loaded poly(lactic-co-glycolic acid) (ASM-PLGA) microspheres through different techniques, including emulsification-solvent evaporation (ESE), Shirasu porous glass membrane emulsification (SPG-ME), and microfluidic method. In vitro and in vivo assessments demonstrated that uniform-sized microspheres generated by the microfluidic process sustainably released ASM throughout 40-days, showing low burst release and significantly improved bioavailability. The results suggest that ASM-PLGA microspheres prepared by the microfluidic method provide an efficient strategy to enhance the drug exposure of ASM as the treatment of chronic neuropsychiatric diseases. It is also evident that this microfluidic strategy has the potential to construct with other drugs, establishing long-acting formulations.